Nine black robes ebook Inside the supreme court's drive to the right and its historic consequences. - Biskupic, Joan (2023)
New York Times Editor's Choice "Biskupic, an accomplished and well-sourced journalist, knows the court as well as anyone now covering it... In her new book Biskupic has done something different and a good deal harder. She has written a group narrative that combines close accounts of the court's public business in the Trump years with a history of its private dramas and conflicts... The deeper message of 'Nine Black Robes' is that even with a new president in office we remain captive to the Age of Trump... A quiet urgency ripples through this informative, briskly paced and gracefully written book." —New York Times Book Review "Biskupic opens a window onto the opaque, insular world of the justices to show an institution sinking gradually into crisis . . . Biskupic is a longtime chronicler of the court, and "Nine Black Robes" puts on display her connections within its chambers." —Washington Post "[Biskupic] knows how to make news and illuminate the personalities atop the judicial org chart . . . The book reveals unseen sausage-making . . ." —Wall Street Journal "Fascinating and informative . . . [Biskupic's] long experience covering the court . . . has put her in an incomparable position to comment on its make-up, historical positions and direction. It has also made her privy to many significant, little-known secrets about Supreme Court personalities and their historical behaviors." —The National Book Review CNN Senior Supreme Court Analyst Joan Biskupic provides an urgent and inside look at the history-making era in the Supreme Court during the Trump and post-Trump years, from its seismic shift to the Right to its controversial decisions, including its reversal of Roe v. Wade, based on access to all the key players. Nine Black Robes displays the inner maneuverings among the Supreme Court justices that led to the seismic reversal of Roe v. Wade and a half century of women's abortion rights. Biskupic details how rights are stripped away or, alternatively as in the case of gun owners, how rights are expanded. Today's bench—with its conservative majority—is desperately ideological. The Court has been headed rightward and ensnared by its own intrigues for years, but the Trump appointments hastened the modern transformation. With unparalleled access to key players, Biskupic shows the tactics of each justice and reveals switched votes and internal pacts that typically never make the light of day, yet will have repercussions for generations to come. Nine Black Robes is the definitive narrative of the country's highest court and its profound impact on all Americans.